Rachel Jacobson's Painful Hip - Marshall Anderson (Association of American Medical Colleges, 2009)
Abstract This is a problem-based learning case for a medical biochemistry-molecular biology course suitable for first- or second-year medical students. The case is that of a young girl who is diagnosed as a compound heterozygote for Gaucher disease and is treated with enzyme replacement therapy. Images have not been not included, as this case would typically be used in a biochemistry-molecular biology course before students have had exposure to histology. With the incorporation of images, the case would be suitable for a histology course or an integrated biochemistry-histology-cell biology course.